Analisa Pengaruh Motivation terhadap Purchase Intention dengan Perception sebagai Variabel Intervening di Toko Obat Tradisional Ban Seng Tong Surabaya - Aldo Newman (Jurnal Strategi Pemasaran, 2014)
The growing of pharmacy, especially for traditional medicine is growing rapidly. As one of the famous traditional medicine store in Surabaya, Ban Seng Tong should understand the views of their consumers mind. This research aims to analyze the impact of Motivation (physiological arousal, emotional arousal, cognitive arousal, environmental arousal) on purchase intention of Ban Seng Tong Surabaya through consideration of perception (sensory systems, exposure, attention, interpretation). This research will be conducted by distributing questionnaires to 130 respondents which are consumer of Ban Seng Tong. Quantitative analysis with path analysis model method were used for the techinal analysis.The result shows there is significant correlation between the motivation and perception to purchase intention in Ban Seng Tong. Perception, Motivation, and Purchase Intention